PENERAPAN BUDAYA 5R (RINGKAS, RAPI, RESIK, RAWAT, RAJIN) UNTUK PENINGKATAN MUTU PEMBELAJARAN DI MI MUHAMMADIYAH KASIHAN 1 TEGALOMBO PACITAN - Lestari, Dwi; Eko Budiono; Katni; Riyanto; Addelia (LPPM STAI Muhammadiyah Probolinggo, 2023)
This study aims to determine the planning, implementation and evaluation of the application of 5R culture in improving the quality of learning at MI Muhamadiyah Kasihan 1 Tegalombo Pacitan. This study uses a field research method with a qualitative descriptive analysis approach with observation, documentation and structured interview techniques. Data analysis used in this study is an analysis technique by reducing data, presenting data and verifying or concluding. The results of this study indicate that the application of 5R culture in improving the quality of learning includes: 1) Classroom management planning that is systematically arranged and prepared by paying attention to stages, procedures, factors and fulfillment of learning facility needs. 2) Implementation of class management by providing and arranging adequate learning facilities, realizing a comfortable classroom design, arranging facilities and learning resources concisely, neat application by educators and students and neat in placing items, as well as consistently well-maintained cleanliness. 3) Evaluation of class management by providing assessment notes on the implementation, monitoring, supervision and improvement of the achieved achievements. In this case specifically in the application of classroom design, neat living, cleanliness of the classroom and environment, and consistency in managing the class in improving the quality of this madrasah.